Genetic and Virulent Difference Between Pigmented and Non-pigmented Staphylococcus aureus - Zhang, Jing; Suo, Yujuan; Zhang, Daofeng; Jin, Fangning; Zhao, Hang; Shi, Chunlei (Frontiers in Microbiology, 2018)
Staphyloxanthin (STX), a golden carotenoid pigment produced by Staphylococcus aureus, is suggested to act as an important virulence factor due to its antioxidant properties. Restraining biosynthesis of STX was considered as an indicator of virulence decline in pigmented S. aureus isolates. However, it is not clear whether natural non-pigmented S. aureus isolates have less virulence than pigmented ones. In this study, it is aimed to compare the pigmented and non-pigmented S. aureus isolates to clarify the genetic and virulent differences between the two groups. Here, 132 S. aureus isolates were divided into two phenotype groups depending on the absorbance (OD450) of the extracted carotenoids. Then, all isolates were subjected to spa typing and multilocus sequence typing (MLST), and then the detection of presence of 30 virulence factors and the gene integrity of crtN and crtM. Furthermore, 24 typical S. aureus isolates and 4 S. argenteus strains were selected for the murine infection assay of in vivo virulence, in which the histological observation and enumeration of CFUs were carried out. These isolates were distributed in 26 sequence types (STs) and 49 spa types. The pigmented isolates were scattered in 25 STs, while the non-pigmented isolates were more centralized, which mainly belonged to ST20 (59%) and ST25 (13%). Among the 54 non-pigmented isolates, about 20% carried intact crtN and crtM genes. The in vivo assay suggested that comparing with pigmented S. aureus, non-pigmented S. aureus and S. argenteus strains did not show a reduced virulence in murine sepsis models. Therefore, it suggested that there were no significant genetic and virulent differences between pigmented and non-pigmented S. aureus.